Didactic conditions for the study of photography in the professional training of future designers (Pedagogy of Higher and Secondary Education, 2009)
Teaching photography to the future designers has its particular features connected to the peculiarities of perception. This article is dedicated to the issue of creating necessary didactic conditions for teaching the an of photography in the process of future designers' professional training.
Keywords: photography; didactic conditions for teaching